Airport check-in counter assignment: a proposed solution. (1st January 2012) - Hwang, Tay-Lin; Jeng, Chi-Ruey; Wang, Sin-Siang
The recent global economic recession and adverse environmental impact have seriously shocked the airline industry. An important task for many airlines is to increase competitiveness. An extremely time-consuming check-in process, especially during peak hours, can significantly degrade passenger perceptions of service quality. Thus, improving the efficiency of check-in counters at airport passenger terminals is a major concern of airport operators and airlines. For example, improving the efficiency of counter assignments by airline reservation systems would reduce manpower needs and enhance operational efficiency. The objective of this study was to establish the operating pattern for airport check-in counter assignments by minimising the operational cost from incurred by the airline and maximising passenger service level with considering the use of kiosk machine and full/part-time duty counter staff. According to the experimental results and sensitivity analyses of actual airline operations data, employing part-time counter staff and using kiosk machines would significantly reduce counter operation cost and improve passenger service quality.